KOHESI GRAMATIKAL DAN LEKSIKAL PADA NOVEL SEPASANG ANGSA PUTIH UNTUK PALUPI KARYA MARLIANA KUSWANTI - Vila Dwi Putriani; Atiqa Sabardila (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
This article aims to: (1) identify the grammatical and lexical aspects of the novel "A Pair of White Angsa For Palupi", and (2) describe the grammatical and lexical aspects of the novel "Sepair of white swans for Palupi". The study used a qualitative approach with a qualitative descriptive method. The technique used in this article is the documentation, listen and note technique. Data collection is done by using data source analysis. The researcher became the main data collection tool and at the same time directly analyzed the collected data. The results showed that there were five data that included grammatical and lexical aspects, which included: First, there were twenty grammatical data in the form of grammatical cohesion markers that appeared, namely references, substitutions, conjunctions, and ellipsis. Second, there are five lexical data in the form of lexical cohesion that appears, namely repetition, antonym. The results of the study indicate that there are grammatical and lexical aspects of the discourse of the novel "A Pair of White Swans for Palupi". Based on the research that has been done, the suggestion to be conveyed to the author is to be careful in the use of pronouns because the use of pronouns that are not appropriate or appropriate can give different or ambiguous meanings. The next suggestion is, it is hoped that there will be further research on grammatical and lexical cohesion.[1] Mahasiswa Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Surakarta[2] Dosen Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Surakarta